2021
DOI: 10.1167/tvst.10.13.26
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Ultrastructural and In Vitro Flow Properties of the PRESERFLO MicroShunt

Abstract: Purpose To measure the in vitro flow properties of the PRESERFLO implant for comparison with the theoretical resistance to flow. Methods The PRESERFLO was designed to control the flow of aqueous humor according to the Hagen-Poiseuille (HP) equation. Scanning electron microscopy (SEM) was performed to analyze the ultrastructure, and flow measurements were carried out using a gravity-flow setup. Results SEM images of the PRESERFLO showed lumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 34 publications
(38 reference statements)
0
23
1
Order By: Relevance
“…Compared with its main competitor, XEN45 (XEN-GGM; Allergan Plc, Parsippany, NJ, EEUU), most studies have reported hypotony rates comparable to PSM (Table 7), despite resistance to flow is 3.4-fold higher through XEN45. 23 Interestingly, in the study conducted by Kim et al, 29 63.2%-83.3% of the patients experienced hypotony, probably due to the high concentration of injected MMC used in the study (70% of the patients received an injection of 0.4 mg/mL without wash-out during an "ab interno"-closed conjunctiva technique). Regarding other filtering surgeries, Tables 8 and 9 show the hypotony rates reported by some studies about trabeculectomy, Express (Alcon, Fort Worth, TX, EEUU) and glaucoma drainage devices.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Compared with its main competitor, XEN45 (XEN-GGM; Allergan Plc, Parsippany, NJ, EEUU), most studies have reported hypotony rates comparable to PSM (Table 7), despite resistance to flow is 3.4-fold higher through XEN45. 23 Interestingly, in the study conducted by Kim et al, 29 63.2%-83.3% of the patients experienced hypotony, probably due to the high concentration of injected MMC used in the study (70% of the patients received an injection of 0.4 mg/mL without wash-out during an "ab interno"-closed conjunctiva technique). Regarding other filtering surgeries, Tables 8 and 9 show the hypotony rates reported by some studies about trabeculectomy, Express (Alcon, Fort Worth, TX, EEUU) and glaucoma drainage devices.…”
Section: Discussionmentioning
confidence: 83%
“…5 The review conducted by Bell et al 22 concluded that with PSM, the trend is to achieve higher rates of success with higher concentrations of MMC, increasing the rate of device-related AEs and reoperations as well. The clinical study with the longest follow-up has been carried out by Batlle et al, 9 reporting the outcomes of 23 patients with primary open angle glaucoma (POAG) 5 years after surgery using 0.4 mg/mL MMC for 3 minutes. The authors concluded that the reduction of the mean IOP and the number of hypotensive medications on the long term after DOI: 10.1097/IJG.0000000000002052 PSM implantation was sustained over time, with a low rate of postoperative complications and no long-term sight-threatening AEs.…”
mentioning
confidence: 99%
“…Although the effect of the 10.0 nylon stent for outflow restriction as a treatment for postoperative prolonged hypotony was previously described [ 23 ], this is the first study to investigate the efficacy of PMS flow restriction in high-risk myopic eyes and its preventive effect on the early hypotony rate. In vitro studies proved that the PMS does not offer hydraulic resistance to outflow similarly to other non-valved shunts, for example, Molteno and Baerveldt [ 24 , 25 , 26 ]; therefore, the only opposition to excessive outflow is the filtration bleb pressure, which, in the early postoperative period, is minimal due to the absence of conjunctival and Tenon fibrosis [ 25 ]. It follows that a major problem of non-valved, bleb-forming, shunt implantation is the early outflow control [ 8 , 9 , 10 , 11 , 24 , 27 , 28 ], and early hypotony is a relatively frequent complication compared to late hypotony, which occurs more rarely.…”
Section: Discussionmentioning
confidence: 99%
“…One reason behind this is that such devices are totally passive, i.e., the drainage of aqueous humor depends upon a fixed hydrodynamic resistance of the shunt [16]. In many cases, however, the hydrodynamic resistance of the shunt may not be optimal which may lead to high IOP, when the resistance in the subconjunctival space is too high (due to the presence of a scar layer), or to overdrainage, if the resistance is too low (resulting in hypotony) [17]. To determine the ideal hydrodynamic resistance that a glaucoma implant must have to overcome these two most common postoperative complications-bleb scarring and hypotony-we developed a model that calculates the pressure in the bleb under these conditions.…”
Section: Plos Onementioning
confidence: 99%